Comparative analysis of Acinetobacter baumannii isolated from hospital wastewater & community tap water: investigating antibiotic resistance and AMR genes - Naser, Nafisa Mehreen; Sakib, Md. Safwan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.